2016
DOI: 10.1021/acsami.6b01197
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonically Enhanced Photocatalytic Hydrogen Production from Water: The Critical Role of Tunable Surface Plasmon Resonance from Gold–Silver Nanoshells

Abstract: Gold-silver nanoshells (GS-NSs) having a tunable surface plasmon resonance (SPR) were employed to facilitate charge separation of photoexcited carriers in the photocalytic production of hydrogen from water. Zinc indium sulfide (ZnIn2S4; ZIS), a visible-light-active photocatalyst, where the band gap varies with the [Zn]/[In] ratio, was used as a model ZIS system (E(g) = 2.25 eV) to investigate the mechanisms of plasmonic enhancement associated with the nanoshells. Three types of GS-NS cores with intense absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 46 publications
0
67
0
Order By: Relevance
“…This technique was utilized to synthesize core-shell nanoparticles by Mancier et al for the generation of Cu@Ag nanoparticles [101]. Similarly, Li and co-workers combined galvanic replacement and diffusion through a protective porous silica shell to synthesize SiO 2 -coated hollow AgAu nanoparticles for use as stable plasmonic agents for NIR activation [1].…”
Section: Other Synthetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique was utilized to synthesize core-shell nanoparticles by Mancier et al for the generation of Cu@Ag nanoparticles [101]. Similarly, Li and co-workers combined galvanic replacement and diffusion through a protective porous silica shell to synthesize SiO 2 -coated hollow AgAu nanoparticles for use as stable plasmonic agents for NIR activation [1].…”
Section: Other Synthetic Methodsmentioning
confidence: 99%
“…The synthesis and properties of metallic nanoparticles (NPs) has been extensively studied over decades, not only because of their unique properties, but also because of their potential applications in catalysis, electronics, optoelectronics, information storage, biosensors, and surface-enhanced Raman spectroscopy (SERS) [1][2][3][4][5][6][7][8][9][10]. Nanoparticles can exist as common structural elements or composites, and they have a wide functional diversity compared to bulk materials.…”
Section: Introductionmentioning
confidence: 99%
“…Note also that an interlayer of SiO2 between the GS-NSs and the ZIS photocatalyst provided another key parameter to control the hydrogen production. Our studies showed that this unique GS-NS@SiO2@ZIS coreshell particles exhibited a unique plasmonic-enhanced photocatalytic hydrogen production [3] [4]. The matching of the absorptions between GS-NSs and ZIS, and the thickness of SiO2 interlayer play important roles on the charge transfer mechanism [4].…”
Section: Extended Abstractmentioning
confidence: 99%
“…Our studies showed that this unique GS-NS@SiO2@ZIS coreshell particles exhibited a unique plasmonic-enhanced photocatalytic hydrogen production [3] [4]. The matching of the absorptions between GS-NSs and ZIS, and the thickness of SiO2 interlayer play important roles on the charge transfer mechanism [4]. However, the coverage, thickness, and crystallinity of ZIS on top of the SiO2 interlayer were not systematically investigated.…”
Section: Extended Abstractmentioning
confidence: 99%
“…The synthesis and properties of metallic nanoparticles (NPs) has been extensively studied over decades, not only because of their unique properties, but also because of their potential applications in catalysis, electronics, optoelectronics, information storage, biosensors, and surfaceenhanced Raman spectroscopy (SERS) [1][2][3][4][5][6][7][8][9][10]. Nanoparticles can exist as common structural elements or composites, and they have a wide functional diversity compared to bulk materials.…”
Section: Introductionmentioning
confidence: 99%